Analizing the poems dedicated to V. Injinnash by kharchin Chin Wang Vandudnamjil - Nasan-Urt Arukhan; V. Yanjindulam (Nomadic Civilization: Historical Research)
Vandudnamjil (1844–1898), known the honored name of Khen Zai was twenty-fourth generation nephew of Zelem, a beneficent official of Chinggis Khan, and an inherited statesman, social activist, writer and poet of the Kharchin ethnicity residing in the Mongoljin Branch or Autonomous Branch of Mongolian nations in Liaoning Province of Fushin, Jun Wang of the late Qing Dynasty’s Kharchin Western Branch, current Kharchin Branch of Ulaanhad City of Inner Mongolian Autonomous Region. In the works of Kharchin Wang Vandudnamjil, the poems written for V. Injinnash, with whom he was a close friend, play a significant role. His poems reflect their close friendship in their youth. In this article, we selected the poems of Kharchin Wang Vandudnamjil for Injinnash Vanchinbal and analyzed content